Joint Associations between Plasma 25-Hydroxyvitamin D, Glycemic Status, and First Stroke in General Hypertensive Adults: Results from the China Stroke Primary Prevention Trial (CSPPT). Issue 1 (23rd November 2021) - Wei, Yaping; Xu, Benjamin; Wang, Zhuo; Zhou, Ziyi; Liu, Lishun; Lin, Tengfei; Song, Yun; Li, Jianping; Zhang, Yan; Huo, Yong; Mao, Guangyun; Wang, Binyan; et al.
ABSTRACT: Background: Associations between vitamin D and stroke remain inconsistent. One major risk factor for stroke is high blood glucose, but the role it plays in this association is not well studied. Objectives: We aimed to evaluate the individual association between plasma 25-hydroxyvitamin D [25(OH)D] and risk of first stroke stratified by fasting blood glucose (FBG), and the joint associations between plasma 25(OH)D, glycemic status, and first stroke in hypertensive adults. Methods: This study was a nested, case-control design utilizing data from the China Stroke Primary Prevention Trial (CSPPT). This analysis included 591 first stroke cases (of which 475 were ischemic stroke, 114 were hemorrhagic stroke, and 2 were uncertain type) and 591 matched controls. The age range of the study population was 45–75 y. The normal FBG (NFG) group had FBG <5.6 mmol/L, and the impaired FBG (IFG) group had FBG ≥5.6 mmol/L and <7.0 mmol/L. Diabetes was defined as participants with FBG ≥7 mmol/L or who were receiving treatment with hypoglycemic agents. ORs (95% CIs) were calculated using unconditional logistic regression models. Results: Multivariable adjusted models revealed an inverse association between quartiles of 25(OH)D and risk of first stroke among participants with NFG, but the opposite trend was observed for those with IFG or diabetes. The largest ORs (>2) were observed among patients with diabetes, compared with the reference group of NFG and high 25(OH)D. Those with NFG and low 25(OH)D (OR = 1.73, 95% CI: 1.22 to 2.44) or those with IFG and high 25(OH)D (OR = 1.74, 95% CI: 1.14 to 2.67) both had a higher risk of total stroke. There was a significant interaction between 25(OH)D and a combined group of IFG and diabetes ( P = 0.001). Similar results were observed for ischemic stroke. Conclusions: In a hypertensive population, the relation between plasma 25(OH)D and risk of first stroke was significantly modified by FBG. This trial was registered at https://www.clinicaltrials.gov as NCT00794885.